A fast-curing liquid raw tape and preparation method thereof
By using the combination of components such as methacrylic modified bisphenol A type epoxy resin in the liquid raw tape, the problem of the difficulty in curing due to contact with oxygen is solved, rapid curing and various performance improvements are achieved, and the appearance, use effect and safety of the product are improved.
Patent Information
- Application Number
- CN202411306913.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The liquid raw tape is difficult to cure due to contact with oxygen in the air, resulting in too large coating area or overflowing from the gaps, causing viscous liquids, affecting the appearance and use effect of the product, and may lead to skin allergies or injuries.
A combination of fast-curing liquid raw tape, including methacrylic modified bisphenol A type epoxy resin, wet activated carbon chimeric silver iodide-zinc powder, nanocopper powder, ethoxylauramine and acid- and alkali-resistant sealant, is used to promote the rapid curing of liquid raw tape through specific preparation methods and combinations.
The rapid curing of liquid raw tape is achieved, and its impact toughness, anti-static properties and acid-base corrosion resistance are improved, which avoids the appearance of viscous liquids, improves the appearance and use effect of the product, and enhances safety.
Smart Images

Figure CN119039919B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a liquid raw tape, in particular to a fast-curing liquid raw tape and a preparation method thereof. Background Art
[0002] Liquid raw tape originated in the 1940s. Currently, it has been widely used in aviation, military industry, general machinery, transportation machinery, oil field pipelines, industrial and civil pipelines, mold manufacturing, etc.
[0003] Since the liquid raw tape will not solidify when it comes into contact with oxygen in the air, it will quickly polymerize and become a cross-linked solid polymer once it is isolated from the air. This feature can be applied to a large area of the liquid raw tape or it will overflow from the bonding gap during actual use. This makes it difficult to solidify due to long-term contact with oxygen in the air, and it will become a viscous liquid. If a large number of workpieces are mixed together, they will cause contamination to each other, seriously affecting the product appearance and actual use effect. At the same time, if the viscous liquid directly contacts the skin of the construction workers, it may also cause skin allergies or even skin injuries. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a fast-curing liquid raw tape; another purpose of the present invention is to provide a method for preparing a fast-curing liquid raw tape.
[0005] Technical solution: A fast-curing liquid raw tape, comprising the following components by weight:
[0006] The composition comprises 100-120 parts of epoxy resin, 20-22 parts of initiator, 2-4 parts of light-promoting exothermic agent, 2-4 parts of accelerator, 4-6 parts of curing accelerator, 2-4 parts of leveling agent, 5-10 parts of antistatic agent, 3-5 parts of toughening agent and 12-15 parts of acid and alkali resistant agent.
[0007] Preferably, the epoxy resin is a methacrylic acid modified bisphenol A epoxy resin, and the preparation method is to add bisphenol A epoxy resin into a reaction bottle, add triphenylphosphine as a catalyst at a weight of 1 / 1200 of the bisphenol A epoxy resin, and heat with methacrylic acid at a weight of 1 / 50 of the bisphenol A epoxy resin to react at 110° C. for 3 hours;
[0008] The curing agent is any one of diethylenetriamine, 4,4'-diaminodiphenylmethane, triethylenetetramine, and pentamethyldiethylenetriamine;
[0009] The light-promoted exothermic agent is wet activated carbon embedded with silver iodide-zinc powder, and the preparation method is as follows: dry activated carbon is added into water and stirred for 5 minutes, filtered, dried to a weight of 120% of the weight of the dry activated carbon, and a mixture of silver iodide-zinc powder with a weight of 1 / 4 of the weight of the dry activated carbon is added under light protection, with the silver iodide / zinc powder = 1 / 3.6 (W / W), and stirred and mixed evenly to obtain wet activated carbon embedded with silver iodide-zinc powder;
[0010] The accelerator is any one of tert-butyl hydroperoxide, benzoyl peroxide, and di-tert-butyl peroxide;
[0011] The curing accelerator is nano copper powder.
[0012] The leveling agent is any one of polydimethylsiloxane, polymethylphenylsiloxane and acrylic resin;
[0013] The antistatic agent is ethoxylated lauryl amide;
[0014] The toughening agent is any one of carboxyl liquid nitrile rubber and liquid silicone rubber;
[0015] The acid and alkali resistant agent is an acid and alkali resistant sealant, wherein the acid and alkali resistant sealant is a commercially available acid and alkali resistant sealant.
[0016] A method for preparing a fast-curing liquid raw tape comprises the following steps:
[0017] S1. Add dry activated carbon into water and stir, filter, and dry to a weight of 120% of the weight of the dry activated carbon. Add a mixture of silver iodide-zinc powder with a weight of 1 / 4 of the weight of the dry activated carbon under light protection, with the silver iodide / zinc powder = 1 / 3.6 (W / W), and stir and mix to obtain wet activated carbon intercalated with silver iodide-zinc powder;
[0018] S2, adding bisphenol A epoxy resin into a reaction bottle, adding triphenylphosphine as a catalyst, adding methacrylic acid and heating to react, to obtain methacrylic acid modified bisphenol A epoxy resin;
[0019] S3. Add the light-promoted exothermic agent, curing agent, curing accelerator, wet activated carbon embedded silver iodide-zinc powder obtained in step S1, leveling agent, antistatic agent, toughening agent, and acid and alkali resistant agent to the methacrylic acid modified bisphenol A epoxy resin obtained in step S2 in sequence under light-proof conditions, and mix well to obtain the product.
[0020] Preferably, in step S1, the weight of water is 5 times the weight of dry activated carbon, the stirring time after adding water is 5 minutes, the drying is forced air drying, the drying temperature is 60° C., the stirring and mixing time is 10 minutes, and the mixing temperature is room temperature.
[0021] Preferably, in step S2, the weight of the catalyst is 1 / 1200 of the weight of the bisphenol A epoxy resin, the weight of methacrylic acid is 1 / 50 of the weight of the bisphenol A epoxy resin, the heating temperature is 110° C., and the reaction time is 3 hours.
[0022] Preferably, in step S3, the mixing method is mechanical stirring, the mixing time is 2 minutes, and the mixing temperature is 10°C.
[0023] Beneficial effects:
[0024] (1) The methacrylic acid-modified bisphenol A epoxy resin used in the present invention has more excellent impact toughness.
[0025] (2) The wet activated carbon embedded with silver iodide-zinc powder added in the present invention has the function of releasing heat when exposed to light, which plays a role in promoting the solidification and condensation of the liquid raw tape.
[0026] (3) The copper powder added in the present invention can react with the residual oxygen in the liquid raw material tape under heating to promote solidification.
[0027] (4) The ethoxylated lauryl amide added in the present invention can play an antistatic role.
[0028] (5) The acid and alkali resistant agent added in the present invention has good acid and alkali resistance properties. After being added and mixed with the system, the liquid raw tape also has excellent acid and alkali corrosion resistance properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the chemical reaction of wet activated carbon embedded with silver iodide-zinc powder when exposed to light in the present invention.
[0030] Figure 2 It is a schematic diagram of the chemical reaction of copper powder eliminating oxygen in the present invention. DETAILED DESCRIPTION
[0031] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0032] Example 1
[0033] The components of a fast-curing liquid raw tape and the weight proportions of each component are:
[0034] Epoxy resin 100 parts;
[0035] 20 parts of 4,4'-diaminodiphenylmethane;
[0036] 2 parts of wet activated carbon intercalated with silver iodide-zinc powder;
[0037] 2 parts of tert-butyl hydroperoxide;
[0038] 4 parts of nano copper powder;
[0039] 2 parts of polymethylphenylsiloxane;
[0040] 5 parts of ethoxylated lauryl amide;
[0041] 3 parts of liquid silicone rubber;
[0042] 12 copies of acid and alkali resistant sealant.
[0043] The specific preparation method is:
[0044] (1) Add 13.79 g of dry activated carbon to 68.95 g of water and stir for 5 min, filter, and dry at 60°C until the weight is 120% of the weight of the dry activated carbon. Add a mixture of silver iodide-zinc powder (silver iodide / zinc powder = 1 / 3.6 (W / W)) with a weight of 1 / 4 of the weight of the dry activated carbon under light protection, and stir to mix evenly to obtain wet activated carbon embedded with silver iodide-zinc powder;
[0045] (2) Add 982.14 g of bisphenol A epoxy resin into a reaction bottle, add 0.83 g of triphenylphosphine as a catalyst, add 17.86 g of methacrylic acid and heat to react to obtain methacrylic acid-modified bisphenol A epoxy resin;
[0046] (3) Add the wet activated carbon-embedded silver iodide-zinc powder obtained in step (1), 200 g of 4,4'-diaminodiphenylmethane, 20 g of tert-butyl hydroperoxide, 40 g of nano copper powder, 20 g of polymethylphenylsiloxane, 50 g of ethoxylated lauryl amide, 30 g of liquid silicone rubber, and 120 g of acid-base resistant sealant to the methacrylic acid-modified bisphenol A epoxy resin obtained in step (2) in sequence under light-proof conditions, and mix well to obtain the mixture.
[0047] Example 2
[0048] The components of a fast-curing liquid raw tape and the weight proportions of each component are:
[0049] Epoxy resin 110 parts;
[0050] 21 parts of 4,4'-diaminodiphenylmethane;
[0051] 3 parts of wet activated carbon intercalated with silver iodide-zinc powder;
[0052] 3 parts of tert-butyl hydroperoxide;
[0053] 5 parts of nano copper powder;
[0054] 3 parts of polymethylphenylsiloxane;
[0055] Ethoxy lauryl amide 7 parts;
[0056] 4 parts of liquid silicone rubber;
[0057] 13 parts of acid and alkali resistant sealant.
[0058] The specific preparation method is:
[0059] (1) Add 20.69 g of dry activated carbon to 103.45 g of water and stir for 5 min, filter, and dry at 60°C until the weight is 120% of the weight of the dry activated carbon. Add a mixture of silver iodide-zinc powder (silver iodide / zinc powder = 1 / 3.6 (W / W)) with a weight of 1 / 4 of the weight of the dry activated carbon under light protection, and stir to mix evenly to obtain wet activated carbon embedded with silver iodide-zinc powder;
[0060] (2) Add 1080.35 g of bisphenol A epoxy resin into a reaction bottle, add 0.91 g of triphenylphosphine as a catalyst, add 19.65 g of methacrylic acid and heat to react to obtain methacrylic acid-modified bisphenol A epoxy resin;
[0061] (3) Add the wet activated carbon-embedded silver iodide-zinc powder obtained in step (1), 210 g of 4,4'-diaminodiphenylmethane, 30 g of tert-butyl hydroperoxide, 50 g of nano copper powder, 30 g of polymethylphenylsiloxane, 70 g of ethoxylated lauryl amide, 40 g of liquid silicone rubber, and 130 g of acid-base resistant sealant to the methacrylic acid-modified bisphenol A epoxy resin obtained in step (2) in sequence under light-proof conditions, and mix well to obtain the mixture.
[0062] Example 3
[0063] The components of a fast-curing liquid raw tape and the weight proportions of each component are:
[0064] Epoxy resin 120 parts;
[0065] 22 parts of 4,4'-diaminodiphenylmethane;
[0066] 4 parts of wet activated carbon intercalated with silver iodide-zinc powder;
[0067] 4 parts of tert-butyl hydroperoxide;
[0068] 6 parts of nano copper powder;
[0069] 4 parts of polymethylphenylsiloxane;
[0070] 10 parts of ethoxylated lauryl amide;
[0071] 5 parts of liquid silicone rubber;
[0072] 15 parts of acid and alkali resistant sealant.
[0073] The specific preparation method is:
[0074] (1) Add 27.58 g of dry activated carbon to 137.9 g of water and stir for 5 min, filter, and dry at 60°C until the weight is 120% of the weight of the dry activated carbon. Add a mixture of silver iodide-zinc powder (silver iodide / zinc powder = 1 / 3.6 (W / W)) with a weight of 1 / 4 of the weight of the dry activated carbon under light protection, and stir to mix evenly to obtain wet activated carbon embedded with silver iodide-zinc powder;
[0075] (2) Add 1178.57 g of bisphenol A epoxy resin into a reaction bottle, add 1.0 g of triphenylphosphine as a catalyst, add 21.43 g of methacrylic acid and heat to react to obtain methacrylic acid-modified bisphenol A epoxy resin;
[0076] (3) Add the wet activated carbon-embedded silver iodide-zinc powder obtained in step (1), 220 g of 4,4'-diaminodiphenylmethane, 40 g of tert-butyl hydroperoxide, 60 g of nano copper powder, 40 g of polymethylphenylsiloxane, 100 g of ethoxylated lauryl amide, 50 g of liquid silicone rubber, and 150 g of acid-base resistant sealant to the methacrylic acid-modified bisphenol A epoxy resin obtained in step (2) in sequence under light-proof conditions, and mix well to obtain the mixture.
[0077] Comparative Example 1
[0078] The same as Example 1, except that the wet activated carbon intercalated silver iodide-zinc powder is not added.
[0079] Comparative Example 2
[0080] Same as Example 1, except that no nano copper powder is added.
[0081] Comparative Example 3
[0082] Same as Example 1, except that ethoxylated lauryl amide was not added.
[0083] Comparative Example 4
[0084] The same as the first embodiment, except that no acid and alkali resistant sealant is added.
[0085] Through the coating curing test, the complete curing time of the liquid raw tape is tested; by immersing the cured liquid raw tape in an acidic aqueous solution of PH=1 for 2 hours, taking it out, rinsing and drying it, and checking whether there are traces of corrosion and discoloration on the surface, its acid resistance is tested; by immersing the cured liquid raw tape in an alkaline aqueous solution of PH=14 for 2 hours, taking it out, rinsing and drying it, and checking whether there are traces of corrosion and discoloration on the surface, its alkali resistance is tested; a 50g weight is placed on the cured liquid raw tape, and it is pulled to slide on the cloth of the same material for 2m, and the cured liquid raw tape is tested for electrostatic field by the SIMCOION handheld FMX-004 electrostatic field tester to test its antistatic properties. The specific data for comparing a fast-curing liquid raw tape prepared in the embodiment and the comparative example are shown in Table 1.
[0086] Table 1 Test results of fast curing liquid raw tape of examples and comparative examples
[0087] Curing time / h Acid soak for 2 hours Alkali soaking Static Electric Field Size / KV Example 1 16.7 No corrosion aging No corrosion aging 0.06 Example 2 16.3 No corrosion aging No corrosion aging 0.04 Example 3 16.0 No corrosion aging No corrosion aging 0.03 Comparative Example 1 23.8 No corrosion aging No corrosion aging 0.06 Comparative Example 2 22.1 No corrosion aging No corrosion aging 0.07 Comparative Example 3 16.8 No corrosion aging No corrosion aging 1.12 Comparative Example 4 16.7 Obvious corrosion aging Obvious corrosion aging 0.06
[0088] As shown in Table 1, a fast-curing liquid raw tape prepared by the present invention, by comparing the data of Example 1, Example 2, and Example 3, it can be seen that the curing time is positively correlated with the concentration of wet activated carbon embedded silver iodide-zinc powder and the content of nano copper powder, and the antistatic energy is positively correlated with the content of ethoxylated lauramide; by comparing the data of Example 1 with that of Comparative Example 1, it can be seen that the addition of wet activated carbon embedded silver iodide-zinc powder can react with light to release heat, which can effectively shorten the curing time; by comparing the data of Example 1 with that of Comparative Example 2, it can be seen that the addition of nano copper powder can remove the oxygen content, which can effectively shorten the curing time; by comparing the data of Example 1 with that of Comparative Example 3, it can be seen that the addition of ethoxylated lauramide can effectively inhibit the generation of static electricity; by comparing the data of Example 1 with that of Comparative Example 3, it can be seen that the addition of acid and alkali resistant sealant can effectively increase the acid and alkali corrosion resistance of the liquid raw tape; by cooperating with each other, the components can have excellent acid and alkali resistance, curing, and antistatic properties.
[0089] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A fast-curing liquid raw tape, characterized in that: It comprises the following components by weight: 100-120 parts of epoxy resin, 20-22 parts of curing agent, 2-4 parts of light-promoting exothermic agent, 2-4 parts of accelerator, 4-6 parts of curing accelerator, 2-4 parts of leveling agent, 5-10 parts of antistatic agent, 3-5 parts of toughening agent, 12-15 parts of acid and alkali resistant agent; Epoxy resin, which is methacrylic acid modified bisphenol A type epoxy resin; The curing agent is any one of diethylenetriamine, 4,4'-diaminodiphenylmethane, triethylenetetramine, and pentamethyldiethylenetriamine; The light-promoted exothermic agent is wet activated carbon embedded with silver iodide-zinc powder; The accelerator is any one of tert-butyl hydroperoxide, benzoyl peroxide, and di-tert-butyl peroxide; The curing accelerator is nano copper powder; The leveling agent is any one of polydimethylsiloxane, polymethylphenylsiloxane and acrylic resin; The antistatic agent is ethoxylated lauryl amide; The toughening agent is any one of carboxyl liquid nitrile rubber and liquid silicone rubber; The acid and alkali resistant agent is an acid and alkali resistant sealant, wherein the acid and alkali resistant sealant is a commercially available acid and alkali resistant sealant.
2. A method for preparing a fast-curing liquid raw tape as claimed in claim 1, characterized in that: The steps include: S1, adding dry activated carbon into water, stirring, filtering, drying, adding silver iodide-zinc powder mixture under light protection, stirring and mixing evenly to obtain wet activated carbon embedded with silver iodide-zinc powder; S2, adding bisphenol A epoxy resin into a reaction bottle, adding triphenylphosphine as a catalyst, adding methacrylic acid and heating to react, to obtain methacrylic acid modified bisphenol A epoxy resin; S3, adding the curing agent, curing accelerator, wet activated carbon embedded silver iodide-zinc powder obtained in step S1, leveling agent, antistatic agent, toughening agent, acid and alkali resistant agent to the methacrylic acid modified bisphenol A type epoxy resin obtained in step S2 in sequence under light-proof conditions, and mixing evenly to obtain.
3. The method for preparing the fast-curing liquid raw tape according to claim 2, characterized in that: In the step S1, the weight of water is 5 times the weight of dry activated carbon, the stirring time after adding water is 5 minutes, the activated carbon is dried to a weight of 120% of the weight of dry activated carbon, the drying is forced air drying, the drying temperature is 60°C, the silver iodide-zinc powder mixture is added and stirred for 10 minutes, and the mixing temperature is room temperature.
4. The method for preparing the fast-curing liquid raw tape according to claim 2, characterized in that: In the step S1, the weight of the silver iodide-zinc powder mixture added is 1 / 4 of the weight of the dry activated carbon.
5. The method for preparing the fast-curing liquid raw tape according to claim 4, characterized in that: In the silver iodide-zinc powder mixture, the silver iodide / zinc powder=1 / 3.6 (W / W).
6. The method for preparing the fast-curing liquid raw tape according to claim 2, characterized in that: In the step S2, the weight of the catalyst is 1 / 1200 of the weight of the bisphenol A epoxy resin, the weight of the methacrylic acid is 1 / 50 of the weight of the bisphenol A epoxy resin, the heating temperature is 110° C., and the reaction time is 3 hours.
7. The method for preparing the fast-curing liquid raw tape according to claim 2, characterized in that: In step S3, the mixing method is mechanical stirring, the mixing time is 2 minutes, and the mixing temperature is 10°C.
Citation Information
Patent Citations
Cure of anaerobic compositions
CN108699400A
Low-halogen rapidly cured conductive adhesive composition and preparation method thereof
CN110272686A